Genetic Diversity of Croton (Codiaeum variegatum (L.) Rumph.ex A. Juss) and Its Offspring Based on RAPD Markers - Mufit Daryatun Asniawati; Aziz Purwantoro (Jurnal Ilmu Pertanian, 2019)
Croton (Puring) is a native  plant of Indonesia which has varied leaf shapes and colors. The diversity of croton increase through hybridization. The information on genetic diversity and relationship between parent and its offspring of crotons is very limited. This study aims to analyze the genetic diversity of cultivar Mawar (MW) and Walet (W) as parent compare to their offspring i.e, Black Marlet (BM), Kingkit 1 (KA), Kingkit 2 (KB), and Kamaratih (KM) using RAPD markers. This study used DNA extraction from the fresh leaf of six cultivars. The next steps were DNA quantification, primary optimization, DNA amplification with PCR, and electrophoresis. Statistical analysis was carried out using Genalex software. A total of 40 primers were screened, out of which 10 were selected for the analysis of genetic diversity. A total of 106 polymorphic bands were generated, ranging from 130 to 1850 bp. The results of RAPD analysis showed that Mawar as female parent had the highest polymorphic bands percentage of 69.01%, while Walet as male parent and its offspring ranged from 31.15 % to 43.94%. The genetic distance of the offspring with Walet ranged from 0.176 to 0.234 and genetic distance of the offspring with Mawar ranged from 0.314 to 0.372. It was indicated that all of offspring were closer to the male parent.